Evaluación de las propiedades mecánicas de materiales compuestos elaborados a partir de cenizas volantes y polímeros reciclados (2015)
In this article evaluates the mechanical properties of composite materials based on fly ash and Coal-fired power plants Termozipa combined with the stretch film (stretch film), linear low density polyethylene post-consumer and partially thermoplastic polymer, crystalline Industrial post. Mixtures were obtained by varying the content of fly ash, 0 to 50 % by weight in each of the three polymeric materials, within a machine type Brabender mixer. The mechanical properties evaluated were: tensile strength, Shore D hardness, and energy absorption, the results obtained indicate that in all cases, as fly ash is added, the mechanical properties increase.